Trends and Mapping of Framing Theory Research: A Bibliometric Analysis using R Studio Biblioshinny - Rosadi, Dian; Prawesti, Anissa Febby Widya; Ali, Maudy Alkahfi; Naqisa, Zikrina Istighfara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Framing Theory is an important approach in communication studies that explains how media construct reality by selecting, highlighting, and presenting certain aspects of an issue. The concept was first introduced by Erving Goffman (1974) in his work Frame Analysis, and was later refined by Robert Entman and other scholars within the context of mass media. Its relevance has grown in the digital media era, where the construction of reality plays a major role in shaping public perception. Numerous studies have applied the framing framework across various issues, including politics, public policy, and international conflicts. This study aims to explore the global development of research on Framing Theory through a bibliometric approach using the Scopus database. The analysis covers publication trends from 2015 to 2024, the most productive authors and countries, institutional affiliations, dominant keywords, and frequently studied themes. The findings reveal that the overall trend of publications on Framing Theory and mass media has increased, despite fluctuations over the years. A significant rise occurred in 2024. Furthermore, the most cited article was on Press Relationship, which received 10 global citations and ranked first. Citation analysis also indicates that no single researcher is entirely dominant, as most authors contributed with a relatively balanced number of publications. Nevertheless, certain scholars, such as Brian J. Bowe, stand out with high citation counts in framing studies. From an institutional perspective, Technische Universität Ilmenau emerged as the most consistent contributor to research on Framing Theory. In addition, keyword analysis (wordclouds) highlights that mass media remains the central theme in studies using the framing framework, alongside other topics related to communication, politics, health, sports, and social issues.